RNA template requirements for target DNA-primed reverse transcription by the R2 retrotransposable element. - Luan, D D (1995)
R2 is a non-long terminal repeat-retrotransposable element that inserts specifically in the 28S rRNA gene of most insects. The single protein encoded by R2 has been shown to contain both site-specific endonuclease and reverse transcriptase activities. Integration of the element involves cleavage of one strand of the 28S target DNA and the utilization of the exposed 3' hydroxyl group to prime the reverse transcription of the R2 RNA transcript. We have characterized the RNA requirement of this target DNA-primed reverse transcription reaction and found that the 250 nucleotides corresponding to the 3' untranslated region of the R2 transcript were necessary and sufficient for the reaction. To investigate the sequence requirements at the site of reverse transcription initiation, a series of RNA templates that contained substitutions and deletions at the extreme 3' end of the RNA were tested. The R2 templates used most efficiently had 3' ends which corresponded to the precise boundary of the R2 element with the 28S gene found in vivo. Transcripts containing short polyadenylated tails (8 nucleotides) were not utilized efficiently. R2 RNAs that were truncated at their 3' ends by 3 to 6 nucleotides were used less efficiently as templates and then only after the R2 reverse transcriptase had added extra, apparently nontemplated, nucleotides to the target DNA. The ability of the reverse transcriptase to add additional nucleotides to the target DNA before engaging the RNA template might be a mechanism for the generation of poly(A) or simple repeat sequences found at the 3' end of most non-long terminal repeat-retrotransposable elements.